Structural Dynamics Response Characteristics of Metro Overlapping Stations under Train Loads in Complex Strata - CHEN Zhining; ZHAO Hongguang; LI Yitao; HU Botao; SHI Naichen (Chengshi guidao jiaotong yanjiu)
[Objective] The structural dynamics response of overlapping metro station under train loads is complex, often resulting in localized amplification of dynamics response and significant difference in dynamics behaviors across various structural locations. Therefore, it is essential to investigate the dynamics response law of overlapping station structures under train loading. [Method] Taking Zhongsheng Station, the cross-shaped intersect-overlapping interchange station on Nanjing Metro Line 7 and Line 10 as the research subject, a three-dimensional refined finite element model under complex stratum conditions is established. Considering the acceleration and deceleration effects of train entering/leaving station, as well as various sequences of train arrival/departure in the overlapping station，the dynamics response law of overlapping station structures under train loading are explored, the station structural deformation, vertical dynamic stress, and acceleration of existing station vertical vibration are analyzed. Multiple measuring points on different station cross-sections are selected, and vibration acceleration data at each measuring point under different working conditions and operating periods are compared through field measurements. [Result & Conclusion] Whether in terms of dynamics displacement and acceleration, or dynamics stress, the dynamics responses in overlapping sections are greater than those in non-overlapping sections. Compared to non-overlapping segments, the maximum dynamics displacement amplification factor at overlapping section measuring points is 4.57, the peak dynamics stress increases by a factor of 2.94, and the maximum amplification factor of vibration acceleration reaches 4.00.